Cytotoxic plant extracts towards insect cells: bioactivity and nanoencapsulation studies for application as biopesticides - Lopes, Ana I. F. (2020)
The potential of plant extracts as bioinsecticides has been described as a promising field of agricultural development. In this work, the extracts of Punica granatum (pomegranate), Phytolacca americana (American pokeweed), Glandora prostrata (shrubby gromwell), Ulex europaeus (gorce), Tagetes patula (French marigold), Camellia japonica red (camellia), Ruta graveolens (rue or herb-of-grace) were obtained, purified, and their activity against Spodoptera frugiperda (Sf9) insect cells was investigated. From the pool of over twenty extracts obtained, comprising different polarities and vegetable materials, less polar samples were shown to be more toxic towards the insect cell line Sf9. Among these, a dichloromethane extract of R. graveolens was capable of causing a loss of viability of over 50%, exceeding the effect of the commercial insecticide chlorpyrifos. This extract elicited chromatin condensation and the fragmentation in treated cells. Nanoencapsulation assays of the cytotoxic plant extracts in soybean liposomes and chitosan nanostructures were carried out. The nanosystems exhibited sizes lower or around 200 nm, low polydispersity, and generally high encapsulation efficiencies. Release assays showed that chitosan nanoemulsions provide a fast and total extract release, while liposome-based systems are suitable for a more delayed release. These results represent a proof-of-concept for the future development of bioinsecticide nanoformulations based on the cytotoxic plant extracts.